Investigation of educational psychology systems, self-efficacy, and student performance : Thematic Content Analysis - Sri Harnani; Cahya Budhi Irawan; Imro'atul Afriani (International Journal of Applied Business and International Management, 2022)
Teachers' education has been examined in the literature on educational psychology. Educational psychology is component of the theory, research, and application of pieces of knowledge.  We investigated whether the predictions of previous studies regarding the relationship between educational psychology and student performance, particularly performance and working memory, could be confirmed. Through a thorough literature review, we compile scientific publications from Science Direct, Google Scholar, and Emerald, as well as books written by education and psychology experts. Using a systematic literature research strategy, we collect scientific papers in order, from selection to analysis. Our research articles were analyzed using content analysis. Because our research is qualitative, the final result is a hypothesis based on the results of previous studies. We conduct research starting with the conceptualization of educational psychology and student work performance. After that, we investigated the relationship between educational psychology systems, self-efficacy, and student performance. After that, we investigated the relationship between educational psychology, self-efficacy, student work performance, and working memory